2016
DOI: 10.4193/rhin15.120
|View full text |Cite
|
Sign up to set email alerts
|

Primary school children often underestimate their nasal obstruction

Abstract: Although NOSE score approximately allow to quantify nasal obstruction, in children, especially between 6 and 9 years of age, an objective measurement of nasal patency should be performed to better define the therapeutic approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
1
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 16 publications
(16 reference statements)
0
21
1
3
Order By: Relevance
“…studied the impact on QoL of AR added to asthma, and female gender was a major determinant of impaired QoL in both diseases. Occasi et al . reported gender differences in the subjective perception of nasal flow in patients between 6 and 14 years old.…”
Section: Discussionmentioning
confidence: 99%
“…studied the impact on QoL of AR added to asthma, and female gender was a major determinant of impaired QoL in both diseases. Occasi et al . reported gender differences in the subjective perception of nasal flow in patients between 6 and 14 years old.…”
Section: Discussionmentioning
confidence: 99%
“…Nasal obstruction is one of the most common reasons that patients visit their doctors, general practitioners and otorhinolaryngologists alike and has a significant impact on the quality of life of patients (5,6) . Blockage is an important outcome of disease not only in nasal disease (7)(8)(9) , but also in rhinosinusitis (10) .…”
Section: Blocked Nosesmentioning
confidence: 99%
“…Indeed, available pediatric studies on the correlation between subjective scores and objective techniques for estimating nasal obstruction provided conflicting results[59,60]. Recently, a pediatric study including 284 children aged 6-14 years showed that a major part of children under-estimate or over-estimate their nasal obstruction and concluded that an objective measurement of nasal patency could improve the clinical management[61]. Here, children were evaluated by anterior active rhinomanometry that provides an accurate evaluation of nasal obstruction or resistance through the measurement of nasal airflow generated by a known pressure gradient[61,62].…”
Section: Diagnosis Of Nar In Childrenmentioning
confidence: 99%
“…Recently, a pediatric study including 284 children aged 6-14 years showed that a major part of children under-estimate or over-estimate their nasal obstruction and concluded that an objective measurement of nasal patency could improve the clinical management[61]. Here, children were evaluated by anterior active rhinomanometry that provides an accurate evaluation of nasal obstruction or resistance through the measurement of nasal airflow generated by a known pressure gradient[61,62]. An alternative technique is represented by acoustic rhinometry, which is basically based upon the amplitude and temporal analysis of the reflections of incident sound waves on the nasal cavities, calculating the cross-sectional area at different depths[63].…”
Section: Diagnosis Of Nar In Childrenmentioning
confidence: 99%